Exclusion in the interests of inclusion: who should stay offline in the emerging world of online justice? - Mulcahy, L; Tsalapatanis, A (Taylor and Francis, 2022)
England and Wales are in the middle of an ambitious court reform programme, a key element of which is the shift to more online hearings in appropriate cases. This raises a series of new questions for the judiciary, not least of which is whether there are circumstances in which a video hearing is unsuitable because a key participant is not able to engage effectively online. This article considers current thinking about the circumstances in which a case should be excluded from the list of online proceedings and compares judicial approaches to what we know of digital disadvantage from the social science literature. The authors draw on emerging judicial statements about threshold competencies, and original research with court staff, regular participants in court hearings and lay users. It is argued that the complex dynamics of digital disadvantage are frequently misunderstood and underestimated. This article makes clear the need for a more in-depth consideration of the multiple ways in which digital disadvantage manifests itself beyond a lack of equipment or skills. In doing so it raises critical questions about what we mean by user perspectives and how the voices of users are being heard.